(untitled) (Research, Society and Development, 2021)
This study aims at developing and validating a scale for measuring overconfidence and optimism in the context of business decisions, with an emphasis on instrument validity. Although overconfidence and optimism are two of the most researched biases in the field of Behavioral Finance, the limits, and intersections between them lack clarity in the available literature and research. The optimism and overconfidence bias items emerged as provisional responses to the following question: In what situations do the optimism and overconfidence biases manifest themselves in the decision making of managers? Exploratory and confirmatory factor analyses were used to create a 13-item scale to measure these biases in the behavior of decision makers. The results of the factor analyses have generated a two-factor structure. The model for measuring the biases of optimism and overconfidence in investment decisions demonstrated a good fit of the model, adequate reliability, convergent validity, and discriminant validity. Optimism obtained the highest average score, followed by overconfidence. The present study resulted in a research instrument capable of identifying the influence of overconfidence and optimism biases in managers’ decision making in organizations. The questionnaire can be used in other empirical studies on behavioral finance, business decision making, and investment decisions.